2021
DOI: 10.3390/su13031515
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Manufacturing: A New Digital Framework for Sustainable Modular Construction

Abstract: This paper explores the notion of the modular building construction site as an applied instance of redistributed manufacturing; in so doing, this research seeks to reduce the environmental footprint of building sites, treating them as small digitally connected subunits. In seeking to provide a whole lifecycle appreciation of a construction project, it is noted that the presence of a framework to provide guidance on the consideration of Internet of Things (IoT) data streams and connected construction objects is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Big Data, and Analytics "circular economy" AND ("big data" OR "big data analytics") AND (construction OR building OR "built environment") 9 0 0 Blockchain Technology "circular economy" AND (blockchain OR "block chain") AND (construction OR building OR "built environment") 9 2 [156,197] Building Information Modelling "circular economy" AND (bim OR "building information model*") AND (construction OR building OR "built environment") 45 26 [43,48,49,54,162,166,168,192,194,195,197,205,206] Digital Marketplaces "circular economy" AND (marketplace OR "market place" OR "digital market*") AND (construction OR building OR "built environment") Geographical Information System "circular economy" AND (gis OR "Geograph* information system") AND (construction OR building OR "built environment") 14 5 [104,106,188,190] Material Passports and Databanks "circular economy" AND (passport OR "material passport" OR "resource passport" OR databank OR database) AND (construction OR building OR "built environment") 60 11 [50,96,180,191,194,195,209,210] The Internet of Things "circular economy" AND (iot OR "internet of things" OR "rfid" OR "wireless sensor networks") AND (construction OR building OR "built environment") 25 8 [54,55,197,201,[211][212][213] Total 265 77…”
Section: Mapped Onto the Cdb Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Big Data, and Analytics "circular economy" AND ("big data" OR "big data analytics") AND (construction OR building OR "built environment") 9 0 0 Blockchain Technology "circular economy" AND (blockchain OR "block chain") AND (construction OR building OR "built environment") 9 2 [156,197] Building Information Modelling "circular economy" AND (bim OR "building information model*") AND (construction OR building OR "built environment") 45 26 [43,48,49,54,162,166,168,192,194,195,197,205,206] Digital Marketplaces "circular economy" AND (marketplace OR "market place" OR "digital market*") AND (construction OR building OR "built environment") Geographical Information System "circular economy" AND (gis OR "Geograph* information system") AND (construction OR building OR "built environment") 14 5 [104,106,188,190] Material Passports and Databanks "circular economy" AND (passport OR "material passport" OR "resource passport" OR databank OR database) AND (construction OR building OR "built environment") 60 11 [50,96,180,191,194,195,209,210] The Internet of Things "circular economy" AND (iot OR "internet of things" OR "rfid" OR "wireless sensor networks") AND (construction OR building OR "built environment") 25 8 [54,55,197,201,[211][212][213] Total 265 77…”
Section: Mapped Onto the Cdb Frameworkmentioning
confidence: 99%
“…From a CE perspective, some of these technologies have received great attention from both practice and academia. Several material passport concepts have emerged, e.g., Madaster [47]; BIM platforms and add-ins have been developed to estimate the recoverability of materials in various design alternatives [48][49][50], and to facilitate efficient data flows and supply chain collaboration [43,51]; recycled materials have been tested in concrete mixes with AM [52]; IoT systems have been designed to track materials for reuse across the life cycle stages [53][54][55].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present study engaged in an extensive review of the relevant literature to identify the key indicators that can be employed to evaluate the efficacy of Distributed Manufacturing in the Construction industry (Minhas et al, 2012;Purvis et al, 2021;Srai et al, 2016;Turner, Oyekan, & Stergioulas, 2021). Based on the insights gleaned from the literature review, a group of experts convened to deliberate and propose a comprehensive list of indicator structures that can be used to evaluate the effectiveness of Distributed Manufacturing in the Construction domain.…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed that in Africa recycling is on the rise, but there seem to be limited standards of the end products, which deter its use. Cluster 6 – turquoise colour is called the “4th industrial revolution (4IR)” (Hoosain et al , 2020; Turner et al , 2021). Finally, technology is the central part of CE transition.…”
Section: Discussionmentioning
confidence: 99%